2010
DOI: 10.1038/ng.660
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study in the Japanese population identifies susceptibility loci for type 2 diabetes at UBE2E2 and C2CD4A-C2CD4B

Abstract: We conducted a genome-wide association study of type 2 diabetes (T2D) using 459,359 SNPs in a Japanese population with a three-stage study design (stage 1, 4,470 cases and 3,071 controls; stage 2, 2,886 cases and 3,087 controls; stage 3, 3,622 cases and 2,356 controls). We identified new associations in UBE2E2 on chromosome 3 and in C2CD4A-C2CD4B on chromosome 15 at genome-wide significant levels (rs7612463 in UBE2E2, combined P = 2.27 × 10⁻⁹; rs7172432 in C2CD4A-C2CD4B, combined P = 3.66 × 10⁻⁹). The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
207
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(225 citation statements)
references
References 36 publications
11
207
1
6
Order By: Relevance
“…Genome-wide association studies (GWASs) and subsequent meta-analyses have identified >56 susceptibility loci for type 2 DM (3)(4)(5)(6)(7)(8)(9)(10)(11). However, these susceptibility loci have been identified predominantly in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) and subsequent meta-analyses have identified >56 susceptibility loci for type 2 DM (3)(4)(5)(6)(7)(8)(9)(10)(11). However, these susceptibility loci have been identified predominantly in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…The Thr-containing protein has a two-fold higher affinity for long-chain fatty acids than the Ala-containing protein (Wanby et al, 2005). The Ala54Thr polymorphism increases free fatty acid transport and triglyceride secretion in vitro (Yamauchi et al, 2010), which are associated with high levels of fasting insulin. Moreover, previous studies have found that FABP2 is a candidate gene possibly implicated in the pathogenesis of T2DM, MetS, and obesity in different ethnic groups (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a number of genetic genome-wide association studies (GWAS) have revealed 40 loci consistently associated with susceptibility to T2D and have rapidly expanded our knowledge of the genetic architecture of this disease (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, the genes located in or near these loci do not fully elucidate the tissue-specific molecular mechanisms underlying the development of T2D.…”
mentioning
confidence: 99%